PERBANDINGAN ABU VULKANIK DAN KAPUR SEBAGAI MATERIAL STABILISASI TANAH LEMPUNG - Aazokhi Waruwu; Arif Darmawandi; Tematius Halawa; Muammar Muammar (Jurnal Proyek Teknik Sipil, 2022)
Clay soil as a subgrade is problematic if it has a low California Bearing Ratio (CBR) value. There are many choices of stabilizing materials that can improve the CBR value, but it is necessary to consider the availability of materials around the project. This study examines partial soil improvement in CBR specimens by differentiating thickness and soil stabilizing materials. The clay stabilization materials used were volcanic ash and lime as much as 6% and 12% of the dry weight of the soil. Laboratory CBR tests were carried out on original soil specimens, 1/3 and 2/3 parts of stabilized soil, and entirely of stabilized soil. The results showed that the CBR value of the stabilized soil with lime was higher than the volcanic ash. The thickness of the stabilized soil has an effect on the CBR value, the overall CBR value is obtained stable in the stabilized soil 2/3 part of the thickness of the soil and the rest is the original compacted soil.